2012
DOI: 10.1136/gutjnl-2011-301913
|View full text |Cite
|
Sign up to set email alerts
|

In vivo targeting of colonic dysplasia on fluorescence endoscopy with near-infrared octapeptide

Abstract: Objective To demonstrate a near-infrared peptide that is highly specific for colonic adenomas on fluorescence endoscopy in vivo. Design A 3 mm diameter endoscope was adapted to deliver 671 nm illumination and collect NIR fluorescence (696–736 nm). Target (QPIHPNNM) and control (YTTNKH) peptides were labeled with Cy5.5, a near-infrared dye, and characterized by mass spectra. The peptides were topically administered separately (100 µM) through the endoscope’s instrument channel into the distal colon of CPC;Apc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…The exact target for this heptapeptide has yet to be determined, so any potential downstream signaling due to peptide binding has not been evaluated. This study made use of endoscopic confocal microscopy, in which only a few square millimeters of colon can be examined, and fluorescein, a suboptimal fluorophore for use in the colon 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact target for this heptapeptide has yet to be determined, so any potential downstream signaling due to peptide binding has not been evaluated. This study made use of endoscopic confocal microscopy, in which only a few square millimeters of colon can be examined, and fluorescein, a suboptimal fluorophore for use in the colon 26 .…”
Section: Discussionmentioning
confidence: 99%
“…14, and the T∕B increased from 4 to ≥ 10. This enhancement elevates the performance of UV-blue excited fluorophores (e.g., FITC) to the level achieved with red and NIR dyes, 16,28 which are excited and fluorescence in spectral regions considered more immune from AF. 6 Indocyanine green, the only FDA-approved NIR fluorescent dye, 55,56 has a hydrophobic, large heptamethine interior that is surrounded by a negatively charged surface shell.…”
Section: Discussionmentioning
confidence: 99%
“…9 It was also shown that topically administered fluorescent molecular probes combined with endoscopic imaging can readily identify cancerous lesions. [8][9][10]27,28 In the diagnosis of HGD and early cancerous lesions in BE, multiple overexpressed cell surface targets, such as epidermal growth-factor receptor (EGFR and ErbB2), hepatocyte growth-factor receptor gene (MET), vascular endothelial growth-factor receptor 2 (VEGFR2), have been reported. 29,30 As a result, the coincident emission signature from multiple fluorescent-labeled probes is expected to provide a more sensitive and a specific disease state diagnosis than a single molecular target for HGD and early cancer detection in BE.…”
Section: Introductionmentioning
confidence: 99%
“…However, a low T/B (≤3) is often reported and is caused by a combination of confounding factors, including the abundant tissue background AF. 8,[13][14][15][16]36,37 Sometimes the background AF signal can be as high as the target signal. It blocks out diagnostic information and reduces the net sensitivity of the molecular probe imaging.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Numerous endoscopic applications for tracking exogenous targeted fluorescence are under investigation, such as detection and diagnosis of early cancerous lesions in Barrett's esophagus, 7 navigation and demarcation of tumor margins during brain surgery, 8,9 and detection of early neoplasia in oral tissue, 10 lung, 11 bladder, 12 and smaller gastrointestinal (GI) ducts. 13 Moreover, translational studies for first-in-human application of fluorescence molecular targets have been demonstrated in colonic dysplasia detection as well as surgical guidance for ovarian cancer. 14,15 Compared to other optical contrast imaging techniques such as narrow band imaging and autofluorescence (AF) imaging, fluorescence molecular imaging with exogenous probes improves specificity for the detection of diseased tissues by targeting specific molecular entities such as overexpressed cell surface proteins at the cellular level.…”
Section: Introductionmentioning
confidence: 99%